Importance of Estuary–Ocean Exchange on Hypoxia in Mid-Lower Chesapeake Bay - Zhengui Wang; Y. Joseph Zhang; Jian Shen; Jeremy M. Testa; Carl Cerco; Lewis Linker; Richard Tian; Wenfan Wu (Estuaries and Coasts, 2026)
In previous water quality modeling studies in Chesapeake Bay, the severity of summer hypoxia tended to be underestimated in the mid-lower Bay area. The underlying reason has not been well understood. In this study, we test a new hypothesis with respect to the estuary–ocean exchange. This hypothesis was motivated by observed high levels of dissolved organic carbon (DOC) near the Bay mouth that, if transported into the Bay, could potentially draw down the dissolved oxygen (DO) in the mid-lower Bay through the microbial respiration of DOC. Using a high-resolution 3D water quality model that includes both the Bay and a portion of the coastal ocean, we provide evidence that supports this hypothesis and demonstrates the important connection between the Bay and the coastal ocean that entrains DOC into the mid-lower Bay during the summer hypoxic season, which leads to a more realistic representation of DO dynamics there. We also outline remaining research questions about the DOC reactivity and sources in the Chesapeake Bay that warrant further study.